Pendampingan Pembuatan Sistem Informasi dan Dokumentasi Berbasis Website Untuk Pelestarian Budaya Lokal Desa Songak - Jumawal; Aris Sudianto; Aida, Saadatul; Selindiani, Silda (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
With the development of information and communication technology (ICT), the use of the internet has become crucial in the preservation of local culture. Songak Village, located in Sakra District, East Lombok Regency, has cultural potential including history, customs, and local arts that need to be documented and promoted. However, the limited information systems and cultural promotion have led to a lack of attention from the younger generation towards cultural heritage. To address this, a website-based information system named "Ning Budaya Songak" was created, aimed at documenting and promoting the village’s culture digitally. The implementation method includes needs analysis, system design and development, testing, and training the community and village officials in using the website. The development results show that the website is effective in providing information about the village's culture, with features that allow the admin to manage content and visitors to access cultural information. The training conducted successfully improved the community's skills in managing this system independently. With this website, Songak Village has a great opportunity to preserve local culture, increase youth participation, and introduce its cultural tourism potential to a wider audience